∫<上x,下0>(t-sint)dt =(1/2t^2+cost)|<上x,下0>=1/2x^2+cosx-1lim(1/2x^2+cosx-1)/ [(e^x^4)-1]=lim(x-sinx)/ (4x^3*e^x^4)=lim(1-cosx)/ (12x^2*e^x^4+16x^6*e^x^4)实在搞不懂 e^x^4 的结构(e^x)^4,还是e^(x^4)刚才由后者算的,累人呀,下面用前者试试lim(1/2x^2+cosx-1)/ [(e^x)^4)-1]=lim(x-sinx)/ (4(e^x)^4=0
利用等价无穷小代换:e^x^4-1~x^4然后再用罗比达法则:=lim [∫<上x,下0>(t-sint)]dt / (x^4)=lim (x-sinx) / (4x^3)=lim(1-cosx)/(4·3x²)=lim(sinx)/(4·3·2x)=1/24
lim [∫<上x,下0>(t-sint)]dt / [(e^x^4)-1] 利用罗比达法则=lim(x-sinx)/(4x³e^(x^4)) =1/4lim(x-sinx)/x³=1/4lim(1-cosx)/3x²=1/4lim(sinx)/6x=1/24limsinx/x=1/24×1=1/24